Топологическая грубость синергетических систем - Оморов, Р.О. (Проблемы управления и информатики, 2012)
Розглянуто метод дослідження грубості динамічних систем, побудований на понятті грубості за Андроновим–Понтрягіним, що називається методом топологічної грубості. Також обговорено застосування методу для досліджень синергетичних систем різної фізичної природи. The method of research of robustness of dynamical systems, based on the concept of robustness by Andronov–Pontryagin and referred to as the method of topological robustness, is considered, as well as its applications to research of synergetic systems of different physical nature.